2021
DOI: 10.1016/j.meegid.2020.104682
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic and age-specific acute lung injury/acute respiratory distress syndrome risk associated with angiotensin-converting enzyme insertion/deletion polymorphisms, implications for COVID-19: A meta-analysis

Abstract: Background The reported association between an insertion/deletion (I/D) polymorphism in the angiotensin-converting enzyme ( ACE ) gene and the risk for acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) remains controversial despite the publication of four meta-analyses on this topic. Here, we updated the meta-analysis with more studies and additional assessments that include adults and children within the context of the coronav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 64 publications
1
19
1
1
Order By: Relevance
“…However, as mentioned above, the relationship between ACE I/D allele frequencies and COVID-19-related mortality is inconclusive. 7 , 10 , 16 In our study, the only significant difference in gender frequency was between the asymptomatic and mid disease patients. In the risk factor analysis, gender had no significant effect on disease severity.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…However, as mentioned above, the relationship between ACE I/D allele frequencies and COVID-19-related mortality is inconclusive. 7 , 10 , 16 In our study, the only significant difference in gender frequency was between the asymptomatic and mid disease patients. In the risk factor analysis, gender had no significant effect on disease severity.…”
Section: Discussioncontrasting
confidence: 49%
“… 7 Similarly, a detailed systematic review published by Pabalan et al noted that the ACE DD genotype might be an important prognostic marker for mortality in Asian COVID-19 patients with acute lung injury/ARDS. 16 In contrast, another meta-analysis with data from 25 different European countries revealed a negative correlation between the frequency of the ACE D allele and the COVID-19 infection rate and mortality. 10 These findings may indicate that the course of COVID-19 may differ geographically.…”
Section: Discussionmentioning
confidence: 95%
“…According to our database analysis, the ACE1 II genotype frequency in a population was significantly negatively correlated with the number of deaths due to SARS-CoV-2 infection, suggesting that the ACE1 II genotype may favorably influence the prevalence and clinical outcome of COVID-19 [1]. In addition, a detailed systematic review published by Pabalan et al shows that the ACE1 DD genotype may be an important prognostic marker for mortality in Asian COVID-19 patients with acute lung injury / ARDS [41]. Similarly, by conducting an epidemiological study in the population from 26 Asian countries, Pati et al showed that the ACE1 D allele is associated with susceptibility to SARS-CoV-2 infection and with the mortality rate [42].…”
Section: Literature and Database Searches (Epidemiological Studies)mentioning
confidence: 69%
“…The frequency of the ACE D allele was reported to be significantly higher in ARDS[ 64 ] but also in the hypoxemic group in Vietnamese patients with SARS related ARDS in the first SARS epidemic[ 65 ]. The association of the ACE D allele/DD genotype with increased mortality is now being increasingly reported in various ethnic groups in SARS-CoV-2 as well[ 59 , 66 ]. This association might reflect the effects the ACE D allele exerts via Ang II on interleukin 6 (IL-6) and plasminogen activator inhibitor-1 (PAI-1) levels (Figure 2 )[ 67 , 68 ].…”
Section: The Ace D Allele / Dd Genotype and Epo Interplay: Implications For Covid-19mentioning
confidence: 99%